PEMANFAATAN LEARNING MANAGEMENT SYSTEM DALAM PROSES PEMBELAJARAN MATEMATIKA DISKRIT - Novi Mardiana; Ahmad Faqih (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
This paper presents the results related to the influence of Mathematics Ability variables and Application-Computer Self-Efficacy (ACSE) students on the Quality of Learning Outcomes in the process of learning Discrete Mathematics by utilizing LMS as a support system. The research method used is Classroom Action Research (CAR), using a quantitative approach. Respondents were third semester students of the Informatics Engineering study program STMIK IKMI Cirebon. The research data were obtained from observations, questionnaires, databases of grades of Calculus and Linear Algebra courses, and recapitulation of student learning outcomes for one semester in Discrete Mathematics lectures. Data analysis was performed using the Dummy Regression method. Based on data analysis, it was found that Mathematical Ability and Application-Computer Self-Efficacy (ACSE) of students had a positive effect on the quality of the results of Discrete Mathematics learning using LMS as a support system.